Cell Membrane-Camouflaged Nanocarriers for Cancer Diagnostic and Therapeutic - Li, Shengxian; Liu, Jianhua; Sun, Mengyao; Wang, Jixue; Wang, Chunxi; Sun, Yinghao (Frontiers in Pharmacology, 2020)
Cell membrane (CM)-camouflaged nanocarriers (CMNPs) are the tools of a biomimetic strategy that has attracted significant attention. With a wide range of nanoparticle cores and CMs available, various creative CMNP designs have been studied for cancer diagnosis and therapy. The various functional CM molecules available allow CMNPs to demonstrate excellent properties such as prolonged circulation time, immune escape ability, reduced systemic toxicity, and homologous targeting ability when camouflaged with CMs derived from various types of natural cells including red and white blood cells, platelets, stem cells, and cancer cells. In this review, we summarize various CMNPs employed for cancer chemotherapy, immunotherapy, phototherapy, and in vivo imaging. We also predict future challenges and opportunities for fundamental and clinical studies.